Онтогенез Psidium littorale Raddi f. Licidum Pilip в условиях защищенного грунта - Ткачук, Л.П.; Фоменко, А.Л. (Промышленная ботаника, 2004)
Seasonal rhythm and life cycle of development of Psidium littorale Raddi. f. lucidum Pilip. have been studied. It has been fixed that long-term influence of low positive temperatures stimulates growth processes. It has been revealed that the more durable florescence period is the more fruits are formed and the more prolonged is the period of their maturation. Long life cycle of plants includes the following periods: latent, pregenerative with three age states (juvenile, immature, virginal) and generative. Studying duration of ontogenesis periods and revealing morphologic peculiarities of plants of this species at the different stages of development enables to use these data in plant systematics for determining species in different age states.